Analysis of Competitive Endogenous Mechanism and Survival Prognosis of Serum Exosomes in Ovarian Cancer Patients Based on Sequencing Technology and Bioinformatics - Li, Xia; Wang, Yurong; Xu, Chunju; Reheman, Xirenguli; Wang, Yuxi; Xu, Rong; Fan, Jiahui; Huang, Xueying; Long, Linna; Yu, Siying; Huang, He (Frontiers in Genetics, 2022)
This study aimed to screen the signaling axis of epigenetic modification in serum exosomes of ovarian cancer patients based on sequencing technology and raw signal analysis, perform an in-depth study of the potential mechanism of action of ovarian cancer, predict potential therapeutic targets and perform a survival prognosis analysis of potential targets.Serum exosomes from three ovarian cancer patients were selected as the experimental group, and from three uterine fibroid patients were selected as the control group. The whole transcriptomes of serum exosomes were used to obtain differentially expressed lncRNAs and mRNAs in ovarian cancer. The databases were used to predict the target genes. Cytoscape software was used to draw a ceRNA network model of epigenetic modification of ovarian cancer serum exosomes, and R language was used for GO and KEGG enrichment analyses of the target genes.The TCGA website was used to download clinical and expression data related to ovarian cancer, and the common potential target genes obtained in the previous period were analyzed for survival.A total of 117 differentially expressed lncRNAs and 513 differentially expressed mRNAs (P < 0.05, |log2 FC|≥ 1.0) were obtained by combining sequencing data and raw signal analysis, and 841 predicted target genes were reciprocally mapped by combining the miRcode database and the miRNA target gene prediction website, resulting in 11 potential target genes related to ovarian cancer (FGFR3, BMPR1B, TRIM29, FBN2, PAPPA, CCDC58, IGSF3, FBXO10, GPAM, HOXA10, LHFPL4). Survival prognosis analysis of the above 11 target genes revealed that the survival curve was statistically significant (P < 0.05) for HOXA10-only genes but not for the other genes. Through enrichment analysis, we found that the above target genes were mainly involved in biological processes such as regulation of transmembrane receptor protein kinase activity, structural molecule activity with elasticity, transforming growth factor-activated receptor activity, and GABA receptor binding, and were mainly enriched in metabolism pathways regulating stem cell pluripotency, bladder cancer, glycerolipid metabolism, central carbon metabolism of cancer, and resistance to EGFR tyrosine kinase inhibitors.The serum exosomal DIO3OS-hsa-miR-27a-3p-HOXA10 epigenetic modification signaling axis affects ovarian cancer development and disease survival prognosis by targeting transcriptional dysregulation pathways in cancer.